The influence of adjustment on academic achievement of adolescent students - Seema Juneja and Dr. Suman Bala (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This study presents a comprehensive review of the influence of adjustment on the academic achievement of adolescent students. Adjustment encompasses various aspects, including emotional regulation, social interactions, family support, school environments, and technology use. These factors play a critical role in shaping adolescents' academic outcomes. The review explores how well-adjusted adolescents, who effectively manage their emotions, maintain supportive relationships, and engage in positive school climates, are more likely to succeed academically. The systematic review examines peer-reviewed articles, books, and scholarly works published up to 2024, focusing on the relationship between adjustment and academic performance among adolescents in India and abroad. The selected literature is critically evaluated based on its objectives, methodology, and findings to identify patterns and trends in the influence of adjustment on academic achievement. By synthesizing the findings from these studies, the paper aims to provide a holistic understanding of the impact of adjustment on the academic success of adolescent students. The review's findings highlight the importance of creating supportive environments that foster emotional, social, and academic adjustment in adolescents. Schools should invest in counseling services, extracurricular activities, and quality teaching to promote a positive climate for students. Parents' active involvement and balanced use of technology are also essential for adolescents' success. By addressing these factors, stakeholders can help adolescents reach their full academic potential.